2011
DOI: 10.1098/rspb.2011.0487
|View full text |Cite
|
Sign up to set email alerts
|

Poor environmental tracking can make extinction risk insensitive to the colour of environmental noise

Abstract: The relative importance of environmental colour for extinction risk compared with other aspects of environmental noise (mean and interannual variability) is poorly understood. Such knowledge is currently relevant, as climate change can cause the mean, variability and temporal autocorrelation of environmental variables to change. Here, we predict that the extinction risk of a shorebird population increases with the colour of a key environmental variable: winter temperature. However, the effect is weak compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 56 publications
5
21
1
Order By: Relevance
“…However, it is not unreasonable to think that one or more of our proposed environmental filters are operating in most animal populations. As a result, an imperfect translation of covariate autocorrelation into PEA may be quite common and recent empirical results are beginning to support this viewpoint (Knape and de Valpine, 2010; Garcia-Carreras and Reuman, 2011; van de Pol et al, 2011; Engen et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is not unreasonable to think that one or more of our proposed environmental filters are operating in most animal populations. As a result, an imperfect translation of covariate autocorrelation into PEA may be quite common and recent empirical results are beginning to support this viewpoint (Knape and de Valpine, 2010; Garcia-Carreras and Reuman, 2011; van de Pol et al, 2011; Engen et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…However, recent work has found that the presence of autocorrelation in a temperature dependent, stage-structured model of Eurasian oystercatchers ( Haematopus ostralegus ) only weakly affected population extinction risk primarily due to nonlinear interactions between demographic rates and environmental covariates that led to poor environmental tracking (van de Pol et al, 2011) and estimates in four other age-structured populations were found to be quite small (Engen et al, 2013). These results provide an empirical example that coupling real life-history complexity to nonlinear environmental responses leads to reductions in the influence of autocorrelated environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The autocorrelation of environmental variables is also changing due to climate change [64]. It would be possible, using a stage-structured model, to compare the relative effects of changes in mean, variance, and autocorrelation of the environment on population dynamics (as done for a single oystercatcher population in [65]). Finally, the sensitivities of are linear approximations of the functions that relate to and , and therefore assume small changes in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…[26]). We, therefore, have a rather poor understanding of how a failure to simultaneously consider microhabitat heterogeneity, behavioural thermoregulation [27], physiological polymorphism [7], and environmental predictability [28] affects forecasts of the ecological impacts of climate change [29].…”
Section: Introductionmentioning
confidence: 99%